2013
DOI: 10.1371/journal.pone.0060197
|View full text |Cite|
|
Sign up to set email alerts
|

TGF-β1 Regulation of Estrogen Production in Mature Rat Leydig Cells

Abstract: BackgroundBesides androgens, estrogens produced in Leydig cells are also crucial for mammalian germ cell differentiation. Transforming growth factor-β1 (TGF-β1) is now known to have multiple effects on regulation of Leydig cell function. The objective of the present study is to determine whether TGF-β1 regulates estradiol (E2) synthesis in adult rat Leydig cells and then to assess the impact of TGF-β1 on Cx43-based gap junctional intercellular communication (GJIC) between Leydig cells.Methodology/Principal Fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 56 publications
2
6
0
Order By: Relevance
“…Even so, TGF-β1 has been shown to increase androgen precursor synthesis from dehydroepiandrosterone as well as the expression of at least three hydroxysteroid dehydrogenases involved in androgen biosynthesis in prostate stromal cells (Piao et al, 2013), predicting its ability to enhance local androgen synthesis within prostate tumors. TGF-β can also decrease aromatase activity in Leydig cells, thus allowing more local DHT accumulation in the absence of testosterone metabolism to 17β-E (Liu et al, 2013). Other recent studies revealed that TGF-β can activate AR in the absence of DHT and, as we show here in osteoblasts, it can cooperate with and enhance AR activation in response to DHT (Yang et al, 2014).…”
Section: Accepted Manuscriptsupporting
confidence: 72%
“…Even so, TGF-β1 has been shown to increase androgen precursor synthesis from dehydroepiandrosterone as well as the expression of at least three hydroxysteroid dehydrogenases involved in androgen biosynthesis in prostate stromal cells (Piao et al, 2013), predicting its ability to enhance local androgen synthesis within prostate tumors. TGF-β can also decrease aromatase activity in Leydig cells, thus allowing more local DHT accumulation in the absence of testosterone metabolism to 17β-E (Liu et al, 2013). Other recent studies revealed that TGF-β can activate AR in the absence of DHT and, as we show here in osteoblasts, it can cooperate with and enhance AR activation in response to DHT (Yang et al, 2014).…”
Section: Accepted Manuscriptsupporting
confidence: 72%
“…Transforming growth factor (TGF)-β has a wide range of biological activities, participates in early embryonic development ( 9 ), cartilage and bone formation, inflammation, interstitial fibrosis, and regulation of immune and endocrine functions ( 10 , 11 ), and tumor formation and development ( 12 , 13 ). Eosinophils and bronchial epithelial cells are the major sources of TGF-β production in the bronchial asthma airway.…”
Section: Introductionmentioning
confidence: 99%
“…Administration of PPARγ agonists (as therapeutic treatment in bronchopulmonary dysplasia) inhibits the canonical WNT/TGF-β pathway and stimulates PPARγ activity [ 72 ]. TGF-β1 as PPARγ, suppresses aromatase activity and the expression of the Cyp19 gene as revealed in adult rat Leydig cells [ 73 ]. According to Gonzales et al [ 74 ] TGF-β1 together with progesterone is involved in the hyperplasia and/or hypertrophy of Leydig cells via Smad1/5 signaling.…”
Section: Discussionmentioning
confidence: 99%